The 3-Dimensional Distribution of Interstellar Dust. Issue Volume 9:Issue S298(2013) (6th January 2014) - Murthy, Jayant
Abstract: A knowledge of the three dimensional distribution of interstellar dust is critical in interpreting all observations of the sky, particularly in the understanding of the structure and morphology of our Galaxy. It has been much easier to map the integrated dust extinction through the Galaxy, which is needed in modeling extragalactic sources, but this yields an overestimate of reddening to Galactic objects. Massive surveys, such as Gaia, present both a problem in that the distribution of interstellar dust must be known in order to model the internal structure of the Galaxy and an opportunity in that multi-color data may be used to deconvolve the dust distribution. I will present the current state of the modeling, which is yet in its early stages.